Developmental language disorder and associated misconceptions : a multi-country perspective - Matić, Ana, logopedinja (Array, 2021)
Although developmental language disorder (DLD) is one of the most common neurodevelopmental disorders, it is often burdened by misconceptions since the general public are unaware of the features of this disorder. Insufficient levels of public awareness and knowledge about DLD highlight the need to adopt appropriate public awareness activities. The aim of this study was to investigate the potential misconceptions associated with the aetiology and recovery of people with DLD in three neighbouring countries - Croatia, Italy, and Slovenia. Additionally, we explored effective ways to promote the spread of accurate information among the public in order to minimise or eliminate false ideas about DLD. To address these specific aims, a public survey was conducted. It was completed by 287 respondents (ages 18 to 60+) with different educational backgrounds (primary and secondary or higher). The results show that the general public in all three countries are misinformed about DLD and hold strong opinions that it is a temporary condition that occurs in childhood, probably as a result of other developmental conditions, and that it will pass either spontaneously or with hard work and proper education. Moreover, the optimal way to increase awareness about DLD was dependent on the age and level of education of the person. Therefore, promoters (ideally researchers and clinicians) must apply specific activities when they target specific groups of people, or use different forms of dissemination activities to reach the broader public, regardless of age and education. The findings reveal a significant lack of knowledge about DLD among the general public and highlight the need for continued awareness campaigns that can target specific groups of people.